My daddy and me - Macnaughton, Tina. (London : Little Tiger Press, 2008)
Little Bear feels brave and tall and happy when he spends time with his father.
On board pages.
1.4
K-3.
K-3
Keywords: Bears -- Juvenile fiction; Father and child -- Juvenile fiction; Bears -- Fiction; Father and child -- Fiction; Stories in rhyme; Bears -- Fiction; Father-child relationship -- Fiction; Stories in rhyme